2014
DOI: 10.1111/cogs.12124
|View full text |Cite
|
Sign up to set email alerts
|

Moving Through Time: The Role of Personality in Three Real‐Life Contexts

Abstract: In English, two deictic space-time metaphors are in common usage: the Moving Ego metaphor conceptualizes the ego as moving forward through time and the Moving Time metaphor conceptualizes time as moving forward toward the ego (Clark, 1973). Although earlier research investigating the psychological reality of these metaphors has typically examined spatial influences on temporal reasoning (e.g., Boroditsky & Ramscar, 2002), recent lines of research have extended beyond this, providing initial evidence that perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…However, there are also alternative views regarding the metaphorical sagittal orientation of time by Chinese people. Given that an increasing number of studies have shown that humans' mental space-time mappings can be influenced by different factors (e.g., Casasanto & Bottini, 2014;Duffy & Evans, 2017;Duffy, Feist, & McCarthy, 2014;Saj et al, 2014;Santiago et al, 2007;Torralbo, Santiago, & Lup añez, 2006), it is possible that Chinese people's mental orientation of sagittal time may not only be affected by linguistic space-time metaphors but may also be shaped by additional influences such as culture (e.g., Boroditsky & Gaby, 2010;Floyd, 2016;Fuhrman & Boroditsky, 2010;Le Guen & Balam, 2012;N uñez et al, 2012;Santiago, Rom an, & Ouellet, 2011). Given that an increasing number of studies have shown that humans' mental space-time mappings can be influenced by different factors (e.g., Casasanto & Bottini, 2014;Duffy & Evans, 2017;Duffy, Feist, & McCarthy, 2014;Saj et al, 2014;Santiago et al, 2007;Torralbo, Santiago, & Lup añez, 2006), it is possible that Chinese people's mental orientation of sagittal time may not only be affected by linguistic space-time metaphors but may also be shaped by additional influences such as culture (e.g., Boroditsky & Gaby, 2010;Floyd, 2016;Fuhrman & Boroditsky, 2010;Le Guen & Balam, 2012;N uñez et al, 2012;Santiago, Rom an, & Ouellet, 2011).…”
Section: Moving Direction Of the Trainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also alternative views regarding the metaphorical sagittal orientation of time by Chinese people. Given that an increasing number of studies have shown that humans' mental space-time mappings can be influenced by different factors (e.g., Casasanto & Bottini, 2014;Duffy & Evans, 2017;Duffy, Feist, & McCarthy, 2014;Saj et al, 2014;Santiago et al, 2007;Torralbo, Santiago, & Lup añez, 2006), it is possible that Chinese people's mental orientation of sagittal time may not only be affected by linguistic space-time metaphors but may also be shaped by additional influences such as culture (e.g., Boroditsky & Gaby, 2010;Floyd, 2016;Fuhrman & Boroditsky, 2010;Le Guen & Balam, 2012;N uñez et al, 2012;Santiago, Rom an, & Ouellet, 2011). Given that an increasing number of studies have shown that humans' mental space-time mappings can be influenced by different factors (e.g., Casasanto & Bottini, 2014;Duffy & Evans, 2017;Duffy, Feist, & McCarthy, 2014;Saj et al, 2014;Santiago et al, 2007;Torralbo, Santiago, & Lup añez, 2006), it is possible that Chinese people's mental orientation of sagittal time may not only be affected by linguistic space-time metaphors but may also be shaped by additional influences such as culture (e.g., Boroditsky & Gaby, 2010;Floyd, 2016;Fuhrman & Boroditsky, 2010;Le Guen & Balam, 2012;N uñez et al, 2012;Santiago, Rom an, & Ouellet, 2011).…”
Section: Moving Direction Of the Trainmentioning
confidence: 99%
“…For example, some believe that the ego faces the past (Alverson, 1994), whereas others believe that the ego can face both the past and the future (Ahrens & Huang, 2002). Given that an increasing number of studies have shown that humans' mental space-time mappings can be influenced by different factors (e.g., Casasanto & Bottini, 2014;Duffy & Evans, 2017;Duffy, Feist, & McCarthy, 2014;Saj et al, 2014;Santiago et al, 2007;Torralbo, Santiago, & Lup añez, 2006), it is possible that Chinese people's mental orientation of sagittal time may not only be affected by linguistic space-time metaphors but may also be shaped by additional influences such as culture (e.g., Boroditsky & Gaby, 2010;Floyd, 2016;Fuhrman & Boroditsky, 2010;Le Guen & Balam, 2012;N uñez et al, 2012;Santiago, Rom an, & Ouellet, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from linguistics hints that time‐ and ego‐moving frames may be associated with assigning different values to future outcomes. Using field studies, Duffy et al () found that people who interpret information through a time‐moving frame show greater conscientiousness and less procrastination than those who interpret the same information through an ego‐moving lens. They undertake unpleasant tasks in the present.…”
Section: Spatial Perception and Time Construalmentioning
confidence: 99%
“…In this article, I ask: Do analogies between time and space reflect, and even influence, how executives address the trade‐off between the short and long term? Field evidence in linguistics associates time‐moving frames with greater conscientiousness and attention to pending events than ego‐moving frames (Duffy, Feist, & McCarthy, ). The future seems to loom larger when it “happens” to us.…”
mentioning
confidence: 99%
“…These findings suggest that people recruit spatial concepts to understand time, thus, indicating unprecedented levels of malleability in human cognition. Extending beyond the earlier work on investigating how spatial experiences influence people's time cognition, recent lines of research have provided preliminary evidence that individual differences such as life styles and emotions may also influence how people reason about events in time (Duffy, Feist & McCarthy, ; Hauser, Carter & Meier, ; Richmond, Wilson & Zinken, ). For instance, Duffy and Feist (, experiment 1) observed that personality might influence an individual's adoption of temporal perspective.…”
Section: Introductionmentioning
confidence: 99%